Effect of mirasol pathogen reduction technology system on immunomodulatory molecules of apheresis platelets. (February 2023) - Valsami, S.; Grouzi, E.; Mochandreou, D.; Pouliakis, A.; Piroula-Godoy, M.; Kokori, S.; Pittaras, T.; Raikou, A.; Politou, M.
Abstract: Pathogen inactivation for platelets by riboflavin system (MIRASOL) efficiently reduces transfusion related pathogen transmission. However little is known about its impact on platelets' immunomodulatory biochemical profile. We aimed was to assess the effects of MIRASOL treatment on platelet quality parameters and immunomodulatory molecules CD62P, RANTES, and CD40L in Single Donor Platelets (SDPs) resuspended in plasma (SDP-P) or T-PAS and additive solution (SDP-A). Twenty nine SDPs (15 SDP-P and 14 SDP-A) were included in the study. Samples were collected before, after MIRASOL treatment and just before transfusion. P-selectin (CD62P), RANTES, and CD40L were tested by ELISA. Platelet products quality assays were also performed. Platelet count/unit decreased after Mirasol treatment by 13 %. The pH of all units decreased over the 5-day storage period but remained above expected limits and the swirling test was positive throughout storage. P-selectin levels were not different between the three different time points in both SDPs-P and SDPs-A while RANTES levels were found to differ statistically significantly at the three different time points in all units and in the SPD-A subgroup. CD40L levels in all SDP products increased slightly during storage but this was not statistically significant. CD62P, RANTES, and CD40L in all time points were elevated in SDPs-A compared to SDPs-P but not at a statistically significant level. In conclusion MIRASOL treatment apart from RANTES increase does not seem to substantially affect platelets associated other cytokines and immunomodulatory molecules namely P-selectin and sCD40L which are implicated in immune transfusion reactions.